Peningkatan Pertumbuhan Ekonomi Daerah melalui Pengembangan Wirausaha Muda di Desa Pemecutan Kaja - Komang Pramana Tri Parartha; Kadek Devi Kalfika Anggria Wardani; Gusi Putu Lestara Permana (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
The impact of the COVID-19 pandemic on the development of self-potential is felt by various groups, especially the younger generation. This is because all schools carry out online learning so that students and students tend to have difficulty in learning and are more likely to be lazy. This is one of the driving forces for the younger generation so that they are less able to develop their potential. In interviews that the author has conducted in Pemecutan Kaja Village, it turns out that there are still many young people who want to help their parents to earn extra income and many of them don't know what to do. Even though they have a lot of potential enough to be used for entrepreneurship, such as making cakes, making snacks, making various types of fast food, opening writing services or typing services, making crafts, and so on. Through their potential, they will tend to be easier in entrepreneurship. In addition to developing self-potential, entrepreneurship in accordance with the potential, interests, and desires will also feel more fun and easier to develop a business. The purpose of this activity is to find out strategies for empowering the potential of the younger generation in developing an entrepreneurial spirit in Pemecutan Kaja Village. The method used in this service is analyzing the community situation, identifying problems, setting work goals, setting problem solving plans, taking social approaches, carrying out activities, and evaluating related activities that have been carried out. From the service carried out, three young people started to open online-based businesses according to their abilities. The businesses include beef jerky, Balinese order, and crispy snacks. These efforts are carried out through e-commerce and social media to facilitate promotion and maintain health protocols.